1026 Prognostic implications of global and regional RV strain in patients with heart failure and conduction delays. (17th January 2020) - Janicijevic, A; Stankovic, I; Zivanic, A; Stefanovic, M; Putnikovic, B; Neskovic, A N
Abstract: Background: Right ventricular (RV) dysfunction is present in a substantial proportion of candidates for cardiac resynchronization therapy (CRT) but its prognostic implication has not been fully determined. We investigated the association of different echocardiographic indices of RV function and survival in patients with heart failure (HF) and conduction delays. Methods: A total of 122 HF patients with bundle branch blocks (BBB), not treated with device therapy, were included in this retrospective observational study. RV function was assessed by measuring the tricuspid annular plane systolic excursion (TAPSE) and RV free wall longitudinal strain (RVFWSL). Patients were followed for cardiac mortality during a median period of 33 months. Results: Both TAPSE ≤ 18 mm and RVFWSL≥-25% were associated with unfavorable long-term survival (log rank p < 0.05 for both, Figure A and B). Importantly, in patients with normal TAPSE, RVFWSL remained predictive of long-term outcome (HR 1.15, 95% CI 1.003-1.327; p = 0.045). In the multivariate regression analysis, only NYHA class (HR 2.21, 95%CI (1.122 – 4.357; p = 0.022) and RVFWSL (HR 1.11, 95%CI 1.029 – 1.204; p = 0.008) were independently associated with cardiac mortality. Significant differences among segmental RVFWLS values were observed, including a basal-to-apical gradient with the highest strain values in the base and the lowest in the apex (Figure C). Conclusions: RV dysfunction is associated with unfavorable survival in HF patients with BBB. RVFWSL appears to be stronger predictor of mortality than TAPSE. Different segments of the RV may contribute differently to RV dysfunction in patients with conduction delays.